The Relationship Between Smartphone Screen Time Duration and Individual Chronotype: A Systematic Literature Review - Lumbantobing, Diego Sergio Giasia; Pramudya, Thalia Altamilano (UI Scholars Hub, 2026)
The rapid increase in smartphone use over the past decade led to prolonged screen time across age groups, particularly during nighttime hours. Exposure to artificial light and pre-sleep digital activities was associated with circadian rhythm disruption and alterations in individual chronotype. This systematic literature review aimed to synthesize empirical evidence on the relationship between smartphone screen time duration and individual chronotype across all age groups and to identify key moderating factors influencing this association. The review was conducted in accordance with PRISMA 2020 guidelines. Literature searches were performed in PubMed, Scopus, and ScienceDirect for studies published between 2015 and 2025. Articles were screened using the Joanna Briggs Institute (JBI). Due to substantial heterogeneity across study designs, populations, and measurement methods, a quantitative–descriptive narrative synthesis was applied. Out of 2,120 identified records, 18 studies met the eligibility criteria. Sixteen studies (88.9%) reported statistically significant associations between longer screen time duration particularly nighttime smartphone use and a greater tendency toward an evening chronotype. The association was strongest and most consistent among adolescents and young adults, whereas weaker or non-significant effects were observed in children and older adults, indicating age as an important biological moderator. Digitally interactive and emotionally stimulating activities, such as social media use and mobile gaming, exerted stronger effects on chronotype shifts than passive screen-based activities. Overall, the findings indicated that the impact of smartphone screen time on chronotype was not uniform but depended on age, type of digital activity, and exposure measurement methods, underscoring the need for targeted, evidence-based digital health interventions.Keywords: Screen time duration, smartphone, chronotype, circadian rhythm, sleep quality